Pengembangan Media Pembelajaran Lectora dalam Menelaah Struktur dan Kebahasaan Puisi Rakyat - Khoirul Muttaqin; Itznaniyah Umie Murniatie (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to develop lectora learning media in studying the structure and language of folk poetry in seventh grade junior high school students. This study uses the Goll, Gall, and Borg R&D methods. The research data was collected through a questionnaire, unstructured interviews, documentation, and observation. This research data analysis utilizes Likert scale calculation. There are three validators in this research, namely media expert, graphic expert, and education practitioner. In addition, students also responded. A small scale trial was conducted on 7F grade Alizzah Batu junior high school students totaling 25 students. Then the usage test was carried out on 7E and 7G grade students totaling 53 students. From the results of the assessment from the instructional media material experts scored 3.01 or could be categorized as